Effects of nucleos(t)ide analogs on hepatitis B surface antigen reduction with interferon‐lambda 3 induction in chronic hepatitis B patients. Issue 7 (12th April 2022) - Umemura, Machiko; Ogawa, Koji; Morikawa, Kenichi; Kubo, Akinori; Tokuchi, Yoshimasa; Yamada, Ren; Kitagataya, Takashi; Shigesawa, Taku; Shimazaki, Tomoe; Kimura, Megumi; Suzuki, Kazuharu; Nakamura, Akihisa; et al.
Abstract: Background & Aims: Benefits of nucleos(t)ide analogs (NAs) on hepatitis B surface antigen (HBsAg) reduction and interferon‐lambda3 (IFN‐λ3) induction are still not known. This study aimed to investigate the effects of NAs on HBsAg reduction and association with serum IFN‐λ3 levels in chronic hepatitis B (CHB) patients. Methods: A total of 91 patients [51 treated with nucleoside analog entecavir hydrate (ETV) and 40 treated with nucleotide analog adefovir dipivoxil (ADV) or tenofovir disoproxil fumarate (TDF)] with clinically evident CHB (chronic hepatitis, 57; liver cirrhosis, 34) were enrolled in this study. Serum IFN‐λ3 levels among patients receiving ETV and ADV/TDF were measured before the initiation of therapy and 1, 3, and 5 years post‐therapy. Results: The change (mean ± standard deviation) in serum HBsAg levels from baseline to year five was −0.38 ± 0.46 and −0.84 ± 0.64 log10 IU/ml in ETV and ADV/TDF groups, respectively ( p = 0.0004). Higher serum IFN‐λ3 levels were observed in ADV/TDF group compared with ETV group during treatment ( p < 0.001). Serum IFN‐λ3 levels showed negative correlation with HBsAg reduction in ADV/TDF group ( r = −0.386, p = 0.038) at week 48. Nucleotide analogs (ADV/TDF) treatment has associated factors with −0.3 log HBsAg decline at 1 year, −0.5 log HBsAg decline at 3 years, and −0.8 log HBsAg decline at 5 years after NAs treatment on multivariate analysis. Conclusions: Nucleotide analog (ADV/TDF) treatment reduced HBsAg levels greater compared with nucleoside analog (ETV) in parallel with IFN‐λ3 induction.